2007
DOI: 10.1074/jbc.m703377200
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Fluorescence Resonance Energy Transfer between Fused Autofluorescent Proteins Reveals Rearrangements of the N- and C-terminal Segments of the Plasma Membrane Ca2+ Pump Involved in the Activation

Abstract: The blue and green fluorescent proteins (BFP and GFP) have been fused at the N-and C-terminal ends, respectively, of the plasma membrane Ca 2؉ pump (PMCA) isoform 4xb (hPMCA4xb). The fusion protein was successfully expressed in yeast and purified by calmodulin affinity chromatography. Despite the presence of the fused autofluorescent proteins BFP-PMCA-GFP performed similarly to the wild-type enzyme with respect to Ca 2؉ -ATPase activity and sensitivity to calmodulin activation. In the autoinhibited state BFP-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
2
35
1
Order By: Relevance
“…On the other hand, mutations of specific residues in the linker segments connecting the A domain with M1, M2, and M3 have been shown to generate deregulated ACA pumps, indicating that these structures are particularly important for autoinhibition (14). Previous work from our laboratory has indicated that also the N-terminal part of the PMCA molecule is involved in autoinhibition (15). Here we present results indicating that residue Glu 99 in the acidic cluster at the N-terminal portion of the M1 transmembrane segment and the C-terminal segment of the h4xb PMCA are critical for decreasing the V max in the autoinhibited state.…”
mentioning
confidence: 99%
“…On the other hand, mutations of specific residues in the linker segments connecting the A domain with M1, M2, and M3 have been shown to generate deregulated ACA pumps, indicating that these structures are particularly important for autoinhibition (14). Previous work from our laboratory has indicated that also the N-terminal part of the PMCA molecule is involved in autoinhibition (15). Here we present results indicating that residue Glu 99 in the acidic cluster at the N-terminal portion of the M1 transmembrane segment and the C-terminal segment of the h4xb PMCA are critical for decreasing the V max in the autoinhibited state.…”
mentioning
confidence: 99%
“…This pump is an integral part of the Ca 2ϩ signaling mechanism (8). It is highly regulated by calmodulin, which activates this protein by binding to an auto-inhibitory region and changing the conformation of the pump from an inhibited state to an activated one (8,9). Crystallization of PMCA is particularly challenging because there is no natural source from which this protein can be obtained in large quantities.…”
mentioning
confidence: 99%
“…This pump is an integral part of the Ca 2ϩ signaling mechanism (1) and is thus a crucial component of cell function. It is highly regulated by calmodulin (CaM), which activates this protein by binding to an auto-inhibitory region (2) and changes the conformation of the pump from an inhibited state to an activated one (2,3).…”
mentioning
confidence: 99%